Let them plan and play: autonomous extension of innovative methods for african resource management - (:unkn) unknown (My University, 2013)
Senior Researcher Nils Ferrand works with farmers and stakeholders to build participatory, role-based models that help decision-makers and policymakers share and manage natural resources in Africa. In this talk, Ferrand discusses the European project, Afromaison, which uses a multi-scale gaming tool called “Wat a Game” that explores and tests management strategies.
Keywords: African Research